A spatial analysis of mental health care in Texas - de Mello-Sampayo, F. (Spatial Economic Analysis, 2016)
This paper discusses competing-destinations formulation of the gravity model for the flows of patients from their residential areas to health supplier regions. This approach explicitly acknowledges the interdependence of the patient between a set of alternative health supplier regions. This competing-destinations based approach may be implemented as a probabilistic demand function or conditional logit model, with a Poisson outcome. A Texas based case study of residential areas and State Mental Hospitals (SMHs) is presented. The results of the estimation do not lend support to the presence of scale effects in SMHs due to the size of population. This result, combined with the negative effect of average length of stay and with the positive effect of the provision of forensic services on patient flows, highlights the problem of caseload growth in SMHs.